Turjawali Berbasis Efektivitas Hukum: Evaluasi Empiris Penegakan Lalu Lintas di Polres Bangka - Edwarddo Fratama; Haidan Angga Kusumah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze the effectiveness of the Traffic Regulation, Guarding, Escort, and Patrol (Turjawali) activities conducted by the Traffic Unit of the Bangka Regional Police in enforcing traffic law and to identify the legal, institutional, infrastructural, social, and cultural factors influencing their implementation. The study employed an empirical legal research method using a descriptive-analytical qualitative approach. Primary data were collected through interviews with traffic police officers, direct observation of Turjawali activities, and operational documentation. Secondary data were obtained from statutory regulations, scientific literature, police reports, and traffic violation statistics. Data were analyzed through reduction, thematic interpretation, presentation, and comparative analysis based on Soerjono Soekanto's theory of legal effectiveness. The findings indicate that Turjawali activities have been relatively effective in reducing traffic violations and accidents in Bangka Regency. Traffic violations declined from 18,342 cases in 2019 to 12,845 cases in 2023, while traffic accidents decreased from 156 to 76 cases during the same period. Nevertheless, the effectiveness of implementation remains constrained by limited personnel, inadequate patrol facilities, low public compliance, and a permissive traffic culture. The study recommends strengthening the Turjawali strategy through risk-based law enforcement, greater utilization of information technology, continuous public education, and stronger collaboration with local governments, schools, and road-user communities to achieve sustainable improvements in traffic safety.